DO QUARTO DE DESPESJO À SALA DE VISITAS: O TESTEMUNHO DO SUJEITO DESLOCADO NOS DIÁRIOS DE CAROLINA MARIA DE JESUS - Pereira da Silva, Eunice; Vieira da Silva, Silvaney; Borges de Souza, Nilsoncley (Inventário, 2025)
This study intends to discuss the testimonial content and the experiences of the subject’s displacement in the works Quarto de despejo (1960) and Casa de alvenaria (1961) by the writer Carolina Maria de Jesus. The purpose of this study is to present the relationship of the writer’s non-belonging to the favela environment in which she was inserted, in the sense of reflecting on what this (place), resulting from a forced migration process, represented for the author. As well as analyzing and discussing the writer’s complaint regarding the issues of inequalities and social exclusion that were evidenced in her diaries, during her period of experience in the Canindé favela in the city of São Paulo, during the decades (1950 to 1960). In order to reach the proposed objectives, we started from the studies and analyzes of the excerpts from (1955 to 1961) according to the writer-character’s feeling of displacement. Therefore, we refer to the theoretical assumptions of researchers Anselmo Peres Alós (2009), Seligmann-Silva (2003), Stuart Hall (2015), among others.